Haematology of air breathing mud eel, Monopterus cuchia (Hamilton, 1822) of Mymensingh and Kishoreganj districts of Bangladesh (Dhaka University Journal of Biological Sciences, 2013)
Haematological profile of air breathing mud eel, Monopterus cuchia (Hamilton) from Mymensinghh and Kishoreganj were determined in the present study. Erythrocytes, lymphocytes, monocytes, neutrophils, eosinophils and platelet were evaluated. Significantly higher (p < 0.05) haemoglobin (Hb) concentration was found in air breathing mud eel of Kishoreganj than that of Mymensinghh area. The haematocrit (HCT), erythrocyte sedimentation rate (ESR), total red blood cells (TRBC), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), total white blood cells (TWBC), lymphocytes, neutrophils, monocytes, eosinophils did not show any significant difference. Findings of the present study showed little variation of haematological profile in air breathing mud eel sampled from Mymensinghh and Kishoreganj.Dhaka Univ. J. Biol. Sci. 22(2): 127-134, 2013 (July)